2011
DOI: 10.1111/j.1556-4029.2011.01723.x
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Suicides Utilizing Helium

Abstract: Retrospective review of cases of suicide involving helium inhalation was undertaken at Forensic Science South Australia over a 25-year period from 1985 to 2009. No cases of helium-related suicides were identified in the first 15 years of the study, with one case between 2000 and 2004 and eight cases between 2005 and 2009. Australian data were also reviewed from 2001 to 2009 that showed 30 cases between January 2001 and June 2005, compared to 79 cases between July 2005 and December 2009, an increase of 163%. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 15 publications
2
36
0
1
Order By: Relevance
“…The significant increase in these deaths that was reported in this study [6] was subsequently confirmed at the national level [7]. In a similar manner, the recent increase in suicides due to helium inhalation noted at Forensic Science SA, in South Australia, over the 25-year period from 1985 to 2009, was identified nationally when Australian data were examined [8].…”
supporting
confidence: 51%
“…The significant increase in these deaths that was reported in this study [6] was subsequently confirmed at the national level [7]. In a similar manner, the recent increase in suicides due to helium inhalation noted at Forensic Science SA, in South Australia, over the 25-year period from 1985 to 2009, was identified nationally when Australian data were examined [8].…”
supporting
confidence: 51%
“…In addition, both cases revealed a medical history of depression treatment, and toxicant tests identified drugs associated with depression which can be regarded as clues to self-infliction [12,13].…”
Section: Discussionmentioning
confidence: 98%
“…Since then, many other cases have been reported after victims have read suicide guides available to the public on the Internet [2][3][4][5][6][7][8][9][10][11]. It appears that this technique causes an accelerated death.…”
Section: Introductionmentioning
confidence: 99%